Patterns of education and supervision of the headmaster in improving discipline and teacher performance - Hendry Faizal; Nur Ahyani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to describe the pattern of guidance and supervision of the principal in improving the discipline and performance of teachers of SMP Negeri 24 Ogan Komering Ulu. This research uses qualitative methods with a descriptive approach. Data collection techniques through observation, interviews, and documentation. The research subjects were the principal, teachers and students. The results of this study indicate that the discipline of teachers at SMP Negeri 24 Ogan Komering Ulu is in a good category, this can be seen from the majority of teachers obeying and carrying out what has become the prevailing rules and norms. Teacher performance is also in the good category as evidenced by the increasing quality of learning and the results of graduates from students who can enter public high schools, if their private schools get top ten report cards. The pattern of guidance and supervision of school principals in improving teacher discipline and performance at SMP Negeri 24 Ogan Komering Ulu is by coaching teacher performance, namely following seminars and training, supervision or supervision of performance in the form of class visits every week and once a month, disciplinary fostering of educational personnel by directly monitoring teacher attendance, providing motivation, and awarding teachers in the form of awards given at each annual event.